Alcohol Septal Ablation for Hypertrophic Obstructive Cardiomyopathy: A case Report (Cardiovascular Journal, 2022)
Alcohol septal ablation (ASA) has shown to be a safe and effective procedure for treatment of symptomatic hypertrophic obstructive cardiomyopathy (HOCM) for more than 20 years with results similar to those of surgical myectomy. The first septal branch of the left anterior descending artery (LAD) is located and 96% alcohol is instilled to induce an artificial myocardial infarction and necrosis at the base of the hypertrophied septum. Now we present our first experience of a patient with HOCM with a very high left ventricular outflow tract gradient who had successful alcohol septal ablation.Cardiovasc j 2022; 15(1): 95-99